Exposure to common infections may shape basal immunity and potentially HIV-1 acquisition amongst a high-risk population in Coastal Kenya - Fwambah, Lynn; Andisi, Cheryl; Streatfield, Claire; Bromell, Rachel; Hare, Jonathan; Esbjörnsson, Joakim; Ndung’u, Thumbi; Sanders, Eduard J.; Hassan, Amin S.; Nduati, Eunice (Frontiers in Immunology, 2024)
Introduction The impact of exposure to endemic infections on basal immunity and susceptibility to HIV-1 acquisition remains uncertain. We hypothesized that exposure to infections such as cytomegalovirus (CMV), malaria and sexually transmitted infections (STIs) in high-risk individuals may modulate immunity and subsequently increase susceptibility to HIV-1 acquisition. Methods A case-control study nested in an HIV-1 negative high-risk cohort from Coastal Kenya was used. Cases were defined as volunteers who tested HIV-1 positive during follow-up and had a plasma sample collected 3 ± 2 months prior to the estimated date of HIV-1 infection. Controls were individuals who remained HIV-1 negative during the follow-up and were matched 2:1 to cases by sex, age, risk group and follow-up time. STI screening was performed using microscopic and serologic tests. HIV-1 pre-infection plasma samples were used to determined exposure to CMV and malaria using enzyme-linked immunosorbent assays and to quantify forty-one cytokines and soluble factors using multiplexing assays. Multiplexing data were analyzed using principal component analysis. Associations between cytokines and soluble factors with subsequent HIV-1 acquisition were determined using conditional logistic regression models. Results and discussion Overall, samples from 47 cases and 94 controls were analyzed. While exposure to malaria (p=0.675) and CMV (p=0.470) were not associated with HIV-1 acquisition, exposure to STIs was (48% [95% CI, 33.3 – 63] vs. 26% [95% CI, 17.3 – 35.9]. Ten analytes were significantly altered in cases compared to controls and were clustered into four principal components: PC1 (VEGF, MIP-1β, VEGF-C and IL-4), PC2 (MCP-1, IL-2 and IL-12p70), PC3 (VEGF-D) and PC4 (Eotaxin-3). PC1, which is suggestive of a Th2-modulatory pathway, was significantly associated with HIV-1 acquisition after controlling for STIs (adjusted odds ratio, (95% CI), p-value: 1.51 [1.14 – 2.00], p=0.004). Elevation of Th2-associated pathways may dampen responses involved in viral immunity, leading to enhanced susceptibility to HIV-1 acquisition. Immunomodulatory interventions aimed at inhibiting activation of Th2-associated pathways may be an additional strategy to STI control for HIV-1 prevention and may reduce dampening of immune responses to vaccination.